Enhancing sugarcane (Saccharum hybrid complex) productivity through modified trench method of planting in sub-tropical India - Singh, A K; Singh, S N; Rao, A K; Sharma, M L (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during autumn seasons of 2007–09 and 2008–10 to study the effect of modified trench method of sugarcane planting at 120 cm apart placing setts across the furrow and covering them with 2.5 cm of soil layer, followed by light irrigation (T5) over other planting methods, viz. conventional furrow planting at 90 cm apart (T1), deep furrow (20 cm) planting at 90 cm apart covering setts with 2.5 cm of soil layer (T2), paired row furrow planting at 120 : 60:120 cm (T3), paired row deep furrow (20 cm) planting at 120: 60:120 cm covering setts with 2.5 cm of soil layer (T4) on the growth, yield and quality of sugarcane (Saccharum hybrid complex) under sub-tropical climatic conditions. Experimental results revealed that T5 planting method produced significantly higher cane yields of 118.7 and 121.7 tonnes/ ha compared with other planting methods during both the years of experimentation. The cane yield thus obtained under T5 was 18.72, 23.87, 21.22 and 27.01% higher than that of T4, T3, T2 and T1 treatments, respectively. Increase in sugar yield exhibited almost similar trend as the yield of cane under different treatments, and accordingly the T5 treatment produced significantly higher sugar yield (14.18 tonnes/ha) than that obtained under rest of the treatments ranging from 10.85 to 11.70 tonnes/ha in the study. Economics of different treatments clearly indicated that by virtue of higher cane yield, the T5 treatment exhibited a net returns and B:C ratio of ` 154 436/ha and 2.23 which were higher to the tune of 18.63 and 10.86, 20.17 and 3.59, 21.20 and 13.00 and 22.73 and 5.83% under T4, T3, T2 and T1 treatments, respectively. Conclusively, since the modified trench method of planting (T5) offers benefit in terms of producing higher yields of cane and sugar over other conventional methods of planting and that would be worth adopting by farmers for increased sugarcane productivity in sub-tropical India.